Trend Analysis of Toponymic Competence: Returning to Tépe, Hungary - Erzsébet Győrffy (Вопросы ономастики)
The results of the previous research conducted by the author in Tépe, Hungary, in 2013, suggested that the population of the village was acquiring fewer and fewer toponyms. This paper provides empirical confirmation of this phenomenon through a follow-up trend analysis carried out in the same village ten years later, in 2023. In both surveys, four generational groups were involved, comprising a total of 7% of the inhabitants. Men and women participated in almost equal numbers. The follow-up study confirms the initial hypothesis: the average toponymic competence (i.e. the relative number of familiar local toponyms) across all generational groups, and in most cases, even individual results of people questioned ten years earlier are now lower than they were in the 2013 survey. Only the group of the youngest participants (those under 20) represents an exception: in their case, we see no difference compared to the earlier data. When examining toponymic competence from the perspective of the name corpus, some changes can also be observed: the proportion of names known to everyone is lower in all generational groups in 2023 than in 2013. The analysis shows that there are more and more place names that can be located by less than half of the respondents. The progressive loss of placenames in Tépe is explained by the author as a result of various natural, economic, and social factors.